The factors affecting antisocial behavior among university students in Universiti Utara Malaysia - Khairul Imran, Khamal Idris (2020)
Antisocial behavior involves a wide variety of inappropriate activities that affect the quality of life in the environment for residents or other individuals living or working in any environments. In other words, antisocial behaviour is typically associated with poor empathy, rebellious, aggressive, risk-taking and irresponsible behaviour, which can happen to both gender, male and female and at any age. A vital component of the outsourcing continuum of disorders is antisocial behaviour that abuses the rights of others such as violence, destruction of property or abuses age-appropriate standards and laws as doing deceitful behaviour, truancy, running away from home. In addition, antisocial behaviour is a specific term that involves not only delinquency and crime but also destructive conduct of children below the age of criminal responsibility, such as violence. As for this paper, the variables that have been discussed are interpersonal communication, peer problem, affection and emotional symptoms. This paper targeted students in Universiti Utara Malaysia as the researcher wanted to see the affect among students in higher education. The questionnaire items were distributed via online google form and it took three weeks to get responds from the students. Data collection was analyzed using Statistical Package for Social Sciences (SPSS) and the outcome shows that there are significant relationship between variables.